1998
DOI: 10.1097/00005650-199807000-00008
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a Drug Use Review Intervention for Sedative Hypnotic Medications

Abstract: The intervention achieved a statistically significant decrease in targeted drug use, and the amount of reduction is likely to have decreased the risk of fractures associated with benzodiazepine use. This study adds to the recent evidence that mailed drug use review interventions can have a desirable impact on patient drug use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 15 publications
0
44
0
Order By: Relevance
“…Act (HIPAA) [2][3][4][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] ; provision of such information is uncommon among programs conducted overseas. Programs outside of the United States commonly use prescriber feedback alone or in combination with educational materials to encourage changes in prescribing practices.…”
Section: S U B J E C T R E V I E Wmentioning
confidence: 99%
See 4 more Smart Citations
“…Act (HIPAA) [2][3][4][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] ; provision of such information is uncommon among programs conducted overseas. Programs outside of the United States commonly use prescriber feedback alone or in combination with educational materials to encourage changes in prescribing practices.…”
Section: S U B J E C T R E V I E Wmentioning
confidence: 99%
“…5,6,28,30,32,[43][44][45] In addition to targeting prescribers, several programs (n = 6) also sent correspondence to pharmacies involved in the care of identified patients. 8,[13][14][15]22,23,46 Jing et al (2011) was the only identified program that included both prescribers and patients as intervention recipients. 3 Six of the 7 aforementioned programs concluded that inclusion of a second recipient to be more effective at achieving the targeted outcome as compared with prescriber recipients alone.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations